Studies in Zebrafish Demonstrate That CNNM2 and NT5C2 Are Most Likely the Causal Genes at the Blood Pressure-Associated Locus on Human Chromosome 10q24.32 - Vishnolia, Krishan K.; Hoene, Celine; Tarhbalouti, Karim; Revenstorff, Julian; Aherrahrou, Zouhair; Erdmann, Jeanette (Frontiers in Cardiovascular Medicine, 2020)
Background: Globally, high blood pressure (BP) is the most important risk factor for cardiovascular disease. Several genome-wide association studies (GWAS) have identified variants associated with BP traits at more than 535 chromosomal loci with genome-wide significance. The post-GWAS challenge is to annotate the most likely causal gene(s) at each locus. Chromosome 10q24.32 is a locus associated with BP that encompasses five genes: CYP17A1, BORCS7, AS3MT, CNNM2, and NT5C2 and warrants investigation to determine the specific gene or genes responsible for the phenotype. Aim: To identify the most likely causal gene(s) associated with BP at the 10q24.32 locus using zebrafish as an animal model. Results: We report significantly higher blood flow, increased arterial pulse, and elevated linear velocity in zebrafish larvae with cnnm2 and nt5c2 knocked down using gene specific splice modification transcriptional morpholinos, compared with controls. No differences in blood flow parameters were observed after as3mt, borcs7 or cyp17a1 knockdown. There was no effect on vessel diameter in animals with any of the four genes knocked down. At the molecular level, expression of hypertension markers (crp and ace) was significantly increased in cnnm2 and nt5c2 knockdown larvae. Further, the results obtained by morpholino knockdown were validated using zebrafish knockout (KO) lines with cnnm2 and nt5c2 deficiency again resulting in higher blood flow, increased arterial pulse, and elevated linear velocity. Analysis of nt5c2a KO larvae demonstrated that lack of this gene resulted in reduced expression of cnnm2a, with reciprocal downregulation of nt5c2a in cnnm2a KO larvae. Staining of whole blood smears from nt5c2 mutants revealed that KO of this gene might be associated with an acute lymphoblastic leukemia phenotype, consistent with literature reports. Additional experiments were designed based on previous literature on cnnm2a mutant zebrafish revealed impaired renal function, high levels of renin, and significantly increased expression of the ren gene, leading us to hypothesize that the observed elevated blood flow parameters may be attributable to triggering of the renin-angiotensin-aldosterone signaling pathway. Conclusion: Our zebrafish data establish CNNM2 and NT5C2 as the most likely causal genes at the 10q24.32 BP locus, and indicate that they trigger separate downstream mechanistic pathways.